THE CONTENT OF SIMULATION TECHNOLOGIES IN THE EDUCATIONAL PROCESS AND THE FORMS, METHODS, AND TOOLS OF THEIR ORGANIZATION - Kosimov Abdulaziz Durdikulovich (International Journal of Literature and Language Studies, 2026)
Abstract: This article examines the pedagogical content, organizational forms, teaching methods, and instructional tools associated with simulation technologies in the educational process. Simulation technologies create an artificial, controlled, and interactive learning environment that reproduces real-life objects, professional situations, processes, and problems. Their application enables students to acquire theoretical knowledge through practical activity, develop professional competencies, make independent decisions, analyze the consequences of their actions, and safely repeat complex operations. The article explains the didactic characteristics of simulation-based learning, including interactivity, modeling, professional orientation, feedback, variability, visualization, and learner autonomy. Individual, pair, group, classroom-based, laboratory-based, distance, blended, and project-based forms of organizing simulation activities are analyzed. Particular attention is paid to problem-based learning, case studies, role-playing, scenario-based learning, virtual experimentation, algorithmic training, reflective analysis, and collaborative problem-solving.